A missão desanalfabetizadora do jornal Gazeta do Norte, em Montes Claros (1918-1938). - Geisa Magela Veloso (2008)
This thesis discusses cultural practices developed in Montes Claros, in the State of Minas Gerais, Brazil, which representations circulated by the newspaper Gazeta do Norte, between 1918 and 1938, with the aim of civilizing, educating and turning the population literate. According to Chartier (1990, 2002) used as theoretical reference, we understand that Cultural History is the history of representations in the social world. These representations are not according to reality, but are the generating matrices of discourses and practices. Considering the concepts of civilization (Elias, 1993) and modernity (Baudrillard, 1989; Le Goff, 1984, 1992), we understand that this newspaper assumes this disilliteracy action as a mission which aims not only to teach how to read and write but to produce a civilized and modern citizen through his insertion in the written culture world. As a result of the research, we noticed that Gazeta do Norte is associated to Escola Normal de Montes Claros (Normal School of Montes Claros) and that this relationship is enhanced from 1923 and produces significant modifications in its education enterprese. Initially organized by the denouncement of problems and advertisement of instruction benefits of education and the act of knowing how to read and write, the militant action of Gazeta do Norte gains new contours along the decade of 1920, acquiring a new pedagogical dimension and as a renovation of teaching methods and comprehensive reading in the decade of 1930. The analyzed cultural practices were influenced by the Escola Nova (New School) movement and begin to claim pedagogical modernity, taking education as a basis in which a new citizen would be forged a civilized individual with a modern mentality, guided by science, conscious of his rights and duties, self-disciplined and productive.